Overcoming mass transfer limitations in cross-linked polyethyleneimine-based adsorbents to enable selective CO2 capture at ambient temperature - Louise Hamdy (Materials Advances, 2022)
New self-supported polyamine CO2 adsorbents are prepared by cross-linking branched polyethyleneimine (PEI) with 2,4,6-tris-(4-bromomethyl-3-fluoro-phenyl)-1,3,5-triazine (4BMFPT). Controlling the degree of cross-linking to ensure abundant free amine functionalities while maintaining a structure conducive to efficient mass transfer is key to accessing high CO2 adsorption and fast kinetics at ambient temperature. The polyamine-based adsorbent, PEI-4BMFPT, 10 : 1 (R), is composed of spherical particles up to 3 μm in diameter and demonstrates fast CO2 uptake of 2.31 mmol g−1 under 1 atm, 90% CO2/Ar at 30 °C. Its CO2/N2 selectivity, predicted by the ideal adsorbed solution theory is 575, equalling that of highly selective metal–organic frameworks. Based on humidified thermogravimetric analysis, it was observed that the presence of water promotes CO2 uptake capacity of 10 : 1 (R) to 3.27 mmol g−1 and results in strong chemisorption; likely by formation of ammonium carbonate and bicarbonate species. It is observed that CO2 uptake enhancement is highly subject to relative humidity and CO2 partial pressure conditions. When adsorption conditions combined low temperatures with low partial pressure CO2, 10 : 1 (R) showed reduced uptake. Tested under breakthrough conditions representative of post-combustion conditions, at 75% RH and 40 °C, CO2 uptake was reduced by 83% of the dry adsorption capacity. This body of work further advances the development of support-free CO2 adsorbents for ambient temperature applications and highlights the drastic effect that relative humidity and CO2 partial pressure have on uptake behaviour.